Distribution of HIV Disease in North Luwu Regency, South Sulawesi, Indonesia in 2023 - Fitra Sawfla Insani; Tina Sesarya (Journal of Health Science and Pharmacy, 2025)
Background: Human Immunodeficiency Virus (HIV) infection remains a significant global public health challenge, including in Indonesia. North Luwu Regency in South Sulawesi has experienced an increasing trend in HIV cases, which is likely associated with low levels of public awareness, engagement in high-risk behaviors, and limited access to comprehensive health services, particularly for prevention, testing, and treatment. Objective: This study aims to analyze the distribution of HIV cases in North Luwu Regency in 2023 based on gender and age group, and to identify factors contributing to the spread of the disease. Method: A quantitative descriptive approach was employed using secondary data obtained from the North Luwu Regency Health Office and the Central Statistics Agency. Data analysis was conducted through graphical visualization and narrative interpretation to examine patterns in HIV case distribution by demographic characteristics. Results: The findings indicate that HIV cases in North Luwu Regency showed an overall increasing trend from 2016 to 2023, with a temporary decline observed during the COVID-19 pandemic period. In 2023, the highest proportion of cases occurred among individuals aged 25–49 years, and the majority of cases were reported among males (66.6%). The estimated population at risk was approximately 5,200 individuals, with 24 newly reported HIV infections during the study year. Conclusion: The observed pattern of HIV transmission in North Luwu Regency reflects a concerning trend that requires intensified public health attention. Strengthening community-based interventions, expanding sexual and reproductive health education, and optimizing surveillance, recording, and reporting systems are essential strategies to reduce HIV transmission and to support the achievement of national HIV control targets.